A Case Study of a Mechanism to Create Local Value Using Local Resources - Nobuta, Katsumi; katsura, Shintaro (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2024)
Purpose: The purpose of this study is to elucidate the mechanism of value creation. While novel strategies for utilizing forest resources are expected worldwide, Japan has the potential to utilize forest resources for tourism. In this paper, we conducted a literature review on advanced forest therapy projects in Japan and conducted interviews with the people involved. Furthermore, a strategic analysis framework of regional economic value chains was used to explain the value creation mechanism of tourism management.